The formation and evolution of the institute governing world trade (Journal of actual problems of jurisprudence, 2018)
The paper examines the history of the formation of the World Trade Organization and the evolution of theinternational legal system on regulation of trade relations.Keywords: World Trade Organization, history of formation, GATT, agreements.